Call of the Void Scale: scale development, validation and psychometric properties - Wiesmann, Lara; Melzer, Laura; Teismann, Tobias (Frontiers in Psychiatry, 2025)
BackgroundThe inexplicable thought of jumping from a bridge, driving into oncoming traffic or walking in front of an oncoming train is known as the Call of the Void (COV) phenomenon. Previous studies have only focused on one COV aspect: the high place phenomenon (HPP), that is a sudden urge to jump when in a high place. In this study, we aimed to develop and validate the Call of the Void Scale (COVS) to measure the prevalence of a variety of these thoughts, their ego-dystonic character and associated safety behaviors.MethodsThe study sample comprised N = 476 participants (71% female, mean age = 30.85 years, standard deviation = 11.5; age range: 18–67 years). Individuals completed the COVS between August 2023 and February 2024 in an anonymous online survey. We analyzed the scale´s factor structure, reliability, and validity through exploratory and confirmatory factor analyses. Bivariate correlations with existing measures of depression, stress, anxiety and suicidal ideation and behavior were calculated to assess convergent validity.ResultsUsing exploratory factor analysis on half of the sample (n1 = 238), we derived a five-factor structure, which was interpreted as representing the frequency of COV in different situations (“frequency HPP”, “frequency car”, “frequency train”), the ego-dystonic character of the thoughts (“ego-dystonia”), and behavior to suppress or manage the thoughts (“safety behavior”). Confirmatory factor analysis on the other half of the sample (n2 = 238) showed a good fit for the five-factor solution. The subscales frequency HPP, frequency car, frequency train and safety behavior were positively correlated with depression, stress, anxiety and suicidal ideation and behavior. The ego-dystonia subscale was only correlated with the safety behavior subscale.ConclusionThe COVS seems to be a valid tool for the assessment of the Call of the Void phenomenon, measuring the prevalence of these thoughts, their ego-dystonic character and associated safety behaviors. The limitations of this study and implications for future research are discussed.